Experience in treating uterine proliferative processes in infertile women - L. A. Shcherbakova; T. A. Gustovarova; A. N. Ivanyan; A. T. Burak (Опухоли женской репродуктивной системы)
The study enrolled 70 reproductive-aged patients with infertility, who had underwent myomectomy for submucous uterine myoma. An immuno- histochemical study showed differences in estrogen and progesterone receptor expressions, proliferative activity determined by Ki-67, and vascular bed areas in both intact endo- and myometrial tissues and submucous uterine myoma ones associated with endometrial hyperplasia. Postoperative hormonal therapy in terms of immunohistochemical evidence was ascertained to reduce the incidence of recurrences and to maintain the reproductive health of a woman.